(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Staphylococcal infections remain a major concern in clinical practice due to their widespread prevalence, ability to cause severe clinical manifestations, and increasing levels of antimicrobial resistance. Staphylococcus aureus, in particular, is responsible for a broad spectrum of community-acquired and hospital-associated infections, ranging from mild skin infections to life-threatening systemic diseases. Accurate and timely laboratory diagnosis is therefore essential for effective patient management and infection control.